Cognitive Status With Frailty Scale In The Elderly People At Santo Yosef Nursing Home Surabaya - Pratama, Kadek I; Christy, Ary; Budianto, Darmawan (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: The increasing life expectancy of the elderly in Indonesia is also followed by an increase in morbidity rate and decreasing the elderly?s physiological function of the body. One of the health problems is decreasing cognitive function. A pathological result of decreasing cognitive function causes frailty in the elderly. Aim : The purpose of this research is to analyze the correlation between cognitive status with frailty scale in the elderly at Santo Yosef Nursing Home Surabaya in 2017. Method : The type of this research is observational analytic with a cross-sectional study and purposive sampling technique. The instrument that been used in this research is the Montreal Cognitive Assessment (MoCA) Indonesian version (MoCa-Ina) and FRAIL Scale. Data collected through the interview method. Result : We used the Rank Spearman correlation test as the analytic test; the result suggesting that there is a significant correlation (p=0,000) with moderate strength of correlation (r=0,593) between cognitive status with the Frailty Scale. Conclusion : From the result, we can conclude that there is a correlation between cognitive status with the Frailty Scale in the elderly